2015
DOI: 10.1021/acs.inorgchem.5b00187
|View full text |Cite
|
Sign up to set email alerts
|

Structures, Thermal Behaviors, and Luminescent Properties of Anhydrous Lanthanum Iodate Polymorphs

Abstract: The structural and thermal studies of six anhydrous lanthanum iodate polymorphs are presented. The variation of the [IO3(-)]:[La(3+)] molar ratio in the starting solution and the evaporation rate of the solution leads to either the centric La(IO3)3(HIO3) or the acentric La(IO3)3(HIO3)1.33 phases. The crystal structure of La(IO3)3(HIO3)1.33 was determined. The thermal treatments of these two phases up to 490 °C lead to β-La(IO3)3, observed at room temperature. To better understand the similar thermal behaviors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(66 citation statements)
references
References 63 publications
9
57
0
Order By: Relevance
“…À ions as those in a-KAu(IO 3 ) 4 (P1) reported by Albrecht-Schmitt et al, [23] but the local symmetry of the [Au(IO 3 ) 4 ]…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…À ions as those in a-KAu(IO 3 ) 4 (P1) reported by Albrecht-Schmitt et al, [23] but the local symmetry of the [Au(IO 3 ) 4 ]…”
Section: Resultsmentioning
confidence: 53%
“…Compared with compound 2,c ompound 1 is more sensitive to the synthetic conditions and requiredasmaller amount of Au(OH) 3 but al argera mount of I 2 O 5 .T he reported aKAu(IO 3 ) 4 may by present in the product randomly in av ery low yield along with al arger amounto fc ompound 2,b ut as ingle phase of a-KAu(IO 3 ) 4 has not been isolated by now on the basis of our experiments. For the preparations of the pure phases of both compounds 1 and 2,alargee xcesso fK IO 3 is necessary.I tw as found that colorless K(IO 3 )(HIO 3 )c rystals were easily grown when the reactionp roducts were cooled to room temperature.…”
Section: Synthesesmentioning
confidence: 97%
See 2 more Smart Citations
“…Differential Scanning Calorimetry. In recent years it is in differential thermal analysis technology (thermal analysis differential, DTA) based on the development of a method can be used for the analysis of the advanced structure of polysaccharides [19]. It can not only describe the sample and reference than the temperature, real-time record heat difference variation with temperature, commonly used in evaluation of polymer thermal stability and compatibility and study of polymer material between the interaction [20,21].…”
Section: Analysis Of the Advanced Structure Of Polysaccharidementioning
confidence: 99%